PRAGMATISME POLITIK PARTAI ISLAM MENJELANG PEMILU 2024 (STUDI KASUS PARTAI KEADILAN SEJAHTERA) - Amir, M Nofrizal; Ilyas, Fauji (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Indonesia is one of the countries with the largest Muslim population in the world. The number of Muslims in Indonesia is recorded at 86.93 percent. This figure indicates that Islam has become the majority religion in Indonesia. However, the tendency of the majority Muslim population in Indonesia does not tend to vote for Islamic parties in political contests. This study aims to examine how Islamic parties can maintain their votes amidst the increasing electability of nationalist-secular parties in Indonesia. This study uses the QDAS approach to analyze news texts using Nvivo Plus 12 software. The results of this study found that Islamic parties such as the Prosperous Justice Party (PKS), the United Development Party (PBB), and the United Development Party (PPP) tend to use the paradigm of political pragmatism to increase their electability and maintain their position in the legislature.